Validation of self-reported oral health among Indonesian adolescents - Ary Agustanti (BMC, 2021)
Abstract Background and aim With the recognition of health as a subjective state, self-reported oral health has been applied in many epidemiological studies. However, the validity of self-reports may vary across different age groups and socio-cultural backgrounds and by using different tools. This study aimed to assess the validity of self-reported oral health of 15-year-old Indonesian adolescents. Materials and methods This study used data from the Indonesian National Oral Health Survey, a part of the Indonesian Basic Health Survey 2018. The study included 572 15-year-old Indonesian adolescents. We compared the presence of clinically assessed dental caries, tooth loss, and fillings following the World Health Organization Basic Health Survey method and questionnaire-based self-reported oral conditions using McNemar test. The sensitivity (Sn), specificity (Sp), and likelihood ratios (LRs) of self-reports were calculated using clinical assessment as the reference standard. The overall accuracy of self-reports in identifying the clinical condition was assessed using the area under the curve (AUC) of a receiver operating characteristic curve. Results Self-reports significantly underestimated the clinical presence of caries (39.3% and 67.1%) and overestimated the clinical presence of tooth loss (9.3% and 4.2%) and filling (4.7% and 2.4%, p < 0.05). All self-reported conditions had higher Sp (at least 70.3%) than Sn (max 54.2%) and the AUC for all self-reported conditions were < 0.7. Self-reporting the presence of fillings had the highest LR+  = 11. Conclusions Self-reporting oral health in Indonesian adolescents had low accuracy. Further studies of other methods of self-reporting are needed before they can be used to assess adolescents’ oral health in epidemiological surveys.